PENGARUH REPETITIVE TRANSCRANIAL MAGNETIC STIMULATION RTMS TERHADAP GANGGUAN FUNGSI KOGNITIF PASCASTROKE ISKEMIK - Novika Azirah Azis,* Jumraini Tammasse,* Abdul Muis* (NEURONA, 2019)
INTRODUCTION THE INCREASING NUMBER OF ISCHEMIC STROKE PATIENTS WHO EXPERIENCE MEMORY DISTURBANCES AND A LONG REHABILITATION PROCESS REQUIRES AN INNOVATION THAT CAN STRENGTHEN BOTH EXISTING THERAPIES MEDICAL THERAPY AND NONINVASIVE STIMULATION OF COGNITIVE REHABILITATION IN THE FORM OF REPETITIVE TRANSCRANIAL MAGNETIC STIMULATION RTMS